Patterns of seedling establishment in an old field - (:unkn) unknown (My University, 1981)
Within 100 years after settlement began (ca. 1830), most forest land in the Milwaukee area had been influenced by agriculture. When the land was cleared for cultivation, trees were occasionally left along property boundaries, on steep slopes or in depressions. These trees served to shade the farmer and his livestock and break the wind. Beginning in the 1930's, urbanization and other changes in land use have resulted in abandonment of cultivated fields and pastures and their regrowth to forest or conversion to other uses. The isolated trees provided a continuing source of tree seed. The presence of an isolated tree in an abandoned field provides an excellent opportunity to study seed dispersal and seedling establishment. This study, undertaken in 1977, examined the distribution of sugar maple (Acer saccharum), white ash (Fraximus americana) and bassmood (Tilia americana) seedlings and was part of a larger study of landscape patterns in southeastern Wisconsin. Seed dispersal and soil and microclimatic effects were examined (O'Donnell 1980).
Keywords: seed dispersal; seedling establishment; old field; sugar maple; Acer saccharum